Characteristics of Solid-State Calcium Ion Sensors Based on Photocurable and Selfplasticising Polyacrylate Matrices - Lee Yook Heng; Elizabeth A.H. Hall (ASEAN Journal on Science and Technology for Development, 2006)
New membrane materials based on cross-linked poly(n-butyl acrylate) (nBA), have been used successfully as calcium ion-selective membranes. These membrane materials possess selfplasticising property and hence do not require plasticisers. The photocurability and good adhesion characteristics of these polymer matrices enable workable solid-state calcium ion sensors to be fabricated by simple photocure procedures employing the calcium ionophore ETH5234 and a lipophilic additive as ion sensing components. The calcium ion-selectivity of the sensors can be controlled by varying the chemical composition of the photocured  membrane. An optimum amount of the cross-linker 2,2-hexanedioldiacrylate (HDDA) and the incorporation of n-heptyl acrylate (nHA) led to improvement in the calcium ion-selectivity. The best calcium ion-selectivity was obtained from a copolymer membrane with composition: nBA = 74 wt-%, nHA = 20 wt-% and HDDA = 0.1 wt-%. The selectivity coefficients of calcium over major cations were: LogKCaPot,Na= -4.4,  LogKCaPot,K = -3.6, LogKCa,PotLi = -5.9, LogKCaPot,Mg= -4.4 with a Nernstian slope (29.1 ± 0.8 mV/decade) under buffered conditions. This potentiometric performance is comparable to other solid-state calcium ion sensors with various plasticised polymer membranes.